A new iteration method for the calculation of the multi-leaf spring - Osipenko, Mikhail Anatolievich; Nyashin, Yuriy Ivanovich (Computational Continuum Mechanics, 2012)
A new iteration method for solving the contact problem of a multi-leaf spring encountered in the classical model is proposed. The spring represents the stack of cantilever beams (leaves) of constant cross-section. The leaves differ in length and thickness, but have the same width. In the absence of loading, the leaves fit each other closely. There is no friction between the leaves. The concentrated force is applied to the tip of the longest leaf. The leaves undergo weak static bending with unbonded contact. The problem consists in finding the forces of interaction between leaves. The proposed method is based on the analytical solution of the generalized contact problem (arbitrary loading) for the two-leaf spring obtained earlier by the authors. This analytical solution is used for adjacent leaves of the multi-leaf spring through iterative adjustment of interaction forces. This method gives a series of novel leaf contact patterns that cannot be obtained by the conventional methods.